A novel reconstructive approach of the lumbar vertebral column from 2D MRI to 3D models - Nerissa Naidoo; Raeesa Khan; Taiceer Abdulwahab; Karl Fredrik Almqvist; Jeyaseelan Lakshmanan; Ivan James Prithishkumar (Elsevier, 2022)
Introduction: Low back pain (LBP), arising from the lumbar vertebral column (LVC), is a global burden, ranking highest in terms of disability. In the United Arab Emirates (UAE), there is a high prevalence of LBP in the adult population. As MRI has emerged as the mainstay in assessment of LVC-related conditions, this study aimed to reconstruct reproducible 3D LVC MRI models from 2D MRI scans. Methods: Following the extraction of serial 2D MRI scan slices from an existing image database, fifty 3D MRI models (n = 50) were retrospectively reconstructed (Mimics Innovation Suite ®) and analyzed through the bootstrapping technique. Results: Lumbar vertebral bodies depicted kidney and oval shapes, with an increasing frequency of the former traced from L1 to L5. Traction (10%) and claw (14%) osteophyte types were noted. The inferior rims of L2 (2%) and L4 (4%) presented with the co-existence of both osteophyte types, which was reflective of the same degenerative process. Morphometric dimensions of L1 were also determined: Anterior vertebral height: 29.6 ± 3.5 mm (28.6-30.5 mm); Posterior vertebral height: 26.8 ± 3.1 mm (25.9-29.6 mm); Superior vertebral width: 40.6 ± 3.8 mm (39.6-41.6 mm); Intervertebral disc height between L1 and L2: 15.9 ± 6.3 mm (14.3-17.7 mm). Conclusion: A proof-of-concept in the reconstructive approach of the LVC was established, which introduces a process through which a normative simulated dataset can be obtained in the extended population. Additionally, these values will assist to detect structural disproportions and changes and contribute to pre-operative planning and artificial intervertebral disc implant design.